Vascular islands during microvascular regression and regrowth in adult networks - Kelly-Goss, Molly R.; Sweat, Richard S.; Azimi, Mohammed S.; Murfee, Walter L. (Frontiers in Physiology, 2013)
Objective: Angiogenesis is the growth of new vessels from pre-existing vessels and commonly associated with two modes: capillary sprouting and capillary splitting. Our previous work suggests vascular island incorporation might be another endothelial cell dynamic involved in microvascular remodeling. Vascular islands are defined as endothelial cell segments disconnected from nearby networks, and their origin remains unclear. The objective of this study was to determine whether vascular islands associated with microvascular regression are involved in network regrowth. Methods: Mesenteric tissues were harvested from adult male Wistar rats according to the experimental groups: unstimulated, post stimulation (10 and 70 days), and 70 days post stimulation + restimulation (3 and 10 days). Stimulation was induced by mast cell degranulation via intraperitoneal injections of compound 48/80. Tissues were immunolabeled for PECAM (endothelial cells), NG2 (pericytes), collagen IV (basement membrane), and BrdU (proliferation). Results: Vascular area per tissue area and length density increased by day 10 post stimulation compared to the unstimulated group. At day 70, vascular area and length density were then decreased, indicating vascular regression compared to day 10. The number of vascular islands at day 10 post stimulation was dramatically reduced compared to the unstimulated group. During regression at day 70, the number of islands increased. The disconnected endothelial cells were commonly bridged to surrounding networks by collagen IV labeling. NG2-positive pericytes were observed along both the islands and the collagen IV tracks. At 3 days post restimulation, vascular islands contained BrdU-positive cells. By day 10 post restimulation, the number of vascular islands was dramatically reduced. Conclusion: The results suggest that vascular islands originating during microvascular regression are capable of proliferation and incorporation into nearby networks during regrowth.